The diversity of locally utilized plants and local botanical knowledge in Central Bengkulu District, Bengkulu Province, Indonesia - WIRYONO WIRYONO; JAPRIYANTO JAPRIYANTO; ERNIWATI ERNIWATI (Biodiversitas Journal of Biological Diversity, 2017)
Wiryono, Japriyanto, Erniwati. 2017. The diversity of locally utilized plants and local botanical knowledge in Central Bengkulu District, Bengkulu Province, Indonesia. Biodiversitas 18: 1589-1595. For thousands of years rural communities have derived from their surrounding plants many products to meet their daily life. Maintaining botanical knowledge is, therefore, essential for the sustainability of rural communities. The objectives of this study were to know the diversity of plants utilized by villagers in Tanjung Terdana Village, Central Bengkulu District, Indonesia, and to describe the botanical knowledge of the villagers. Data were collected through interview with two key informants and 64 respondents. The results showed that 75 of plant species were used by villagers for ten purposes, namely medicine (53 species), firewood (41), food (32), construction (23), ornament (8), handycraft (6), hedge (6), custom (6) forage (3), and food coloring (1). On average, respondents could identify 70% of the 50 plants shown to them, and almost all respondents (98%) could identify plants for food. Older respondents spent more time in garden and knew more plant names and uses than the younger ones. Gender or time spent in electronic entertainment did not affect the botanical knowledge. Respondents unfinishing elementary school knew more plants than those finishing schools, may be because they were older. This study implied that activities in the garden can maintain the local botanical knowledge.